Social stability risk of public-private-partnership waste-to-energy incineration projects in China: Social network analysis of stakeholders - Ke Wang; Kebei Liu; Yanjie Du; Tao Zheng (Sustainable Futures)
In China, Public-Private Partnership (PPP) projects for waste incineration power generation have significantly aided social and economic development; however, they often result in societal risks that compromise the stability of society. A key element influencing the risk to social stability in PPP projects for trash incineration power generation is the diversity of the parties involved and their intricate interrelationships. Prior research on the risk to societal stability has mostly concentrated on risk identification and evaluation, ignoring stakeholder relationships and the connections between various risks. Through a review of the literature and stakeholder interviews, this study examines the pertinent risk factors and their interactions identified by social networks for PPP projects for waste incineration power generation. A multi-channel project financial system, effective group event avoidance mechanism, and comprehensive project schedule control system are suggested to reduce threats to social stability. To provide guidance for the social stability risk management of PPP projects for waste incineration power production in China, this study integrates stakeholders with risk management using social network analysis.